An azobenzene container showing a definite folding – synthesis and structural investigation - Adam, Abdulselam; Mehrparvar, Saber; Haberhauer, Gebhard (Beilstein Journal of Organic Chemistry, 2019)
The combination of photo-switchable units with macrocycles is a very interesting field in supramolecular chemistry. Here, we present the synthesis of a foldable container consisting of two different types of Lissoclinum macrocyclic peptides which are connected via two azobenzene units. The container is controllable by light: irradiation with UV light causes a switching process to the compact cis,cis-isomer, whereas by the use of visible light the stretched trans,trans-isomer is formed. By means of quantum chemical calculations and CD spectroscopy we could show that the trans→cis isomerization is spatially directed; that means that one of the two different macrocycles performs a definite clockwise rotation to the other, caused by irradiation with UV light. For the cis→trans isomerization counterclockwise rotations are found. Furthermore, quantum chemical calculations reveal that the energy of the cis,cis-isomer is only slightly higher than the energy of the cis,trans-isomer. This effect can be explained by the high dispersion energy in the compact cis,cis-isomer.
Keywords: azobenzene; macrocycles; molecular switch

Supramolecular Chemistry - Steed, J. W.; Atwood, J. L. (John Wiley & Sons, 2009)

(untitled) - Michael, J. P.; Pattenden, G. (Angew. Chem., Int. Ed. Engl., 1993)

(untitled) - Jolliffe, K. A. (Supramol. Chem., 2005)

(untitled) - Young, P. G.; Clegg, J. K.; Bhadbhade, M.; Jolliffe, K. A. (Chem. Commun., 2011)

(untitled) - Young, P. G.; Jolliffe, K. A. (Org. Biomol. Chem., 2012)

(untitled) - Dungan, V. J.; Ngo, H. T.; Young, P. G.; Jolliffe, K. A. (Chem. Commun., 2013)

(untitled) - Butler, S. J.; Jolliffe, K. A. (Org. Biomol. Chem., 2011)

(untitled) - Liu, X.; Ngo, H. T.; Ge, Z.; Butler, S. J.; Jolliffe, K. A. (Chem. Sci., 2013)

(untitled) - Haberhauer, G.; Oeser, T.; Rominger, F. (Chem. – Eur. J., 2005)

(untitled) - Schnopp, M.; Haberhauer, G. (Eur. J. Org. Chem., 2009)

(untitled) - Bartfai, T.; Lu, X.; Badie-Mahdavi, H.; Barr, A. M.; Mazarati, A.; Hua, X.-Y.; Yaksh, T.; Haberhauer, G.; Ceide, S. C.; Trembleau, L.; Somogyi, L.; Kröck, L.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Ceide, S. C.; Trembleau, L.; Haberhauer, G.; Somogyi, L.; Lu, X.; Bartfai, T.; Rebek, J., Jr (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Jantos, K.; Rodriguez, R.; Ladame, S.; Shirude, P. S.; Balasubramanian, S. (J. Am. Chem. Soc., 2006)

(untitled) - Tao, H.; Weng, Y.; Zhuo, R.; Chang, G.; Urbatsch, I. L.; Zhang, Q. (ChemBioChem, 2011)

(untitled) - Singh, S.; Prasad, N. R.; Kapoor, K.; Chufan, E. E.; Patel, B. A.; Ambudkar, S. V.; Talele, T. T. (ChemBioChem, 2014)

(untitled) - Szewczyk, P.; Tao, H.; McGrath, A. P.; Villaluz, M.; Rees, S. D.; Lee, S. C.; Doshi, R.; Urbatsch, I. L.; Zhang, Q.; Chang, G. (Acta Crystallogr., Sect. D: Biol. Crystallogr., 2015)

(untitled) - Shukla, S.; Abel, B.; Chufan, E. E.; Ambudkar, S. V. (J. Biol. Chem., 2017)

(untitled) - Pattenden, G.; Thompson, T. (Chem. Commun., 2001)

(untitled) - Singh, Y.; Sokolenko, N.; Kelso, M. J.; Gahan, L. R.; Abbenante, G.; Fairlie, D. P. (J. Am. Chem. Soc., 2001)

(untitled) - Singh, Y.; Stoermer, M. J.; Lucke, A. J.; Glenn, M. P.; Fairlie, D. P. (Org. Lett., 2002)

(untitled) - Sato, K.; Itoh, Y.; Aida, T. (Chem. Sci., 2014)

(untitled) - Sato, K.; Itoh, Y.; Aida, T. (J. Am. Chem. Soc., 2011)

(untitled) - Schnopp, M.; Ernst, S.; Haberhauer, G. (Eur. J. Org. Chem., 2009)

(untitled) - Comba, P.; Gahan, L. R.; Haberhauer, G.; Hanson, G. R.; Noble, C. J.; Seibold, B.; van den Brenk, A. L. (Chem. – Eur. J., 2008)

(untitled) - Comba, P.; Dovalil, N.; Hanson, G. R.; Harmer, J. R.; Noble, C. J.; Riley, M. J.; Seibold, B. (Inorg. Chem., 2014)

(untitled) - Kay, E. R.; Leigh, D. A.; Zerbetto, F. (Angew. Chem., Int. Ed., 2007)

Molecular Switches - Feringa, B. L.; Browne, W. R. (Wiley-VCH, 2011)

(untitled) - Erbas-Cakmak, S.; Leigh, D. A.; McTernan, C. T.; Nussbaumer, A. L. (Chem. Rev., 2015)

(untitled) - Qu, D.-H.; Wang, Q.-C.; Zhang, Q.-W.; Ma, X.; Tian, H. (Chem. Rev., 2015)

(untitled) - Rau, H. (Angew. Chem., Int. Ed. Engl., 1973)

(untitled) - Mathews, M.; Zola, R. S.; Hurley, S.; Yang, D.-K.; White, T. J.; Bunning, T. J.; Li, Q. (J. Am. Chem. Soc., 2010)

(untitled) - Beharry, A. A.; Woolley, G. A. (Chem. Soc. Rev., 2011)

(untitled) - Bandara, H. M. D.; Burdette, S. C. (Chem. Soc. Rev., 2012)

(untitled) - Merino, E.; Ribagorda, M. (Beilstein J. Org. Chem., 2012)

(untitled) - Natali, M.; Giordani, S. (Chem. Soc. Rev., 2012)

(untitled) - Wang, Y.; Urbas, A.; Li, Q. (J. Am. Chem. Soc., 2012)

(untitled) - Sun, R.; Xue, C.; Ma, X.; Gao, M.; Tian, H.; Li, Q. (J. Am. Chem. Soc., 2013)

(untitled) - Abendroth, J. M.; Bushuyev, O. S.; Weiss, P. S.; Barrett, C. J. (ACS Nano, 2015)

(untitled) - Fihey, A.; Perrier, A.; Browne, W. R.; Jacquemin, D. (Chem. Soc. Rev., 2015)

(untitled) - Bisoyi, H. K.; Li, Q. (Chem. Rev., 2016)

(untitled) - Glinsky-Olivier, N.; Guinchard, X. (Synthesis, 2017)

(untitled) - Griffiths, J. (Chem. Soc. Rev., 1972)

(untitled) - Haberhauer, G.; Kallweit, C. (Angew. Chem., Int. Ed., 2010)

(untitled) - Takaishi, K.; Kawamoto, M.; Tsubaki, K.; Furuyama, T.; Muranaka, A.; Uchiyama, M. (Chem. – Eur. J., 2011)

(untitled) - Takaishi, K.; Muranaka, A.; Kawamoto, M.; Uchiyama, M. (J. Org. Chem., 2011)

(untitled) - Takaishi, K.; Muranaka, A.; Kawamoto, M.; Uchiyama, M. (Org. Lett., 2012)

(untitled) - Haberhauer, G.; Kallweit, C.; Wölper, C.; Bläser, D. (Angew. Chem., Int. Ed., 2013)

(untitled) - Núñez, I.; Merino, E.; Lecea, M.; Pieraccini, S.; Spada, G. P.; Rosini, C.; Mazzeo, G.; Ribagorda, M.; Carreño, M. C. (Chem. – Eur. J., 2013)

(untitled) - Adam, A.; Haberhauer, G. (J. Am. Chem. Soc., 2017)

(untitled) - Mehrparvar, S.; Adam, A.; Haberhauer, G. (Eur. J. Org. Chem., 2018)

(untitled) - Haberhauer, G.; Pintér, Á.; Oeser, T.; Rominger, F. (Eur. J. Org. Chem., 2007)

(untitled) - Haberhauer, G. (Angew. Chem., Int. Ed., 2007)

(untitled) - Becke, A. D. (Phys. Rev. A, 1988)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Miehlich, B.; Savin, A.; Stoll, H.; Preuss, H. (Chem. Phys. Lett., 1989)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Grimme, S. (Chem. – Eur. J., 2012)

(untitled) - Ditchfield, R.; Hehre, W. J.; Pople, J. A. (J. Chem. Phys., 1971)

(untitled) - Hehre, W. J.; Ditchfield, R.; Pople, J. A. (J. Chem. Phys., 1972)

(untitled) - Schäfer, A.; Horn, H.; Ahlrichs, R. (J. Chem. Phys., 1992)

(untitled) - Weigend, F.; Ahlrichs, R. (Phys. Chem. Chem. Phys., 2005)

Gaussian 16, Revision A.03 (Gaussian, Inc., 2016)